1,5-Di-meth-oxy-naphthalene. - Marfo-Owusu, E; Thompson, A (2013)
The title compound, C12H12O2, lies across an inversion centre. The mol-ecular structure suggests that the meth-oxy groups in the 1- and 5-positions of the naphthalene moiety do not significantly distort the planar conformation of the ring system, which has a maximum deviation of 0.0025 (9) Å. In the crystal, mol-ecules pack in a herringbone arrangement in layers parallel to (100) and with chains propagating along [101] formed by very weak C-H⋯O inter-actions.